Launching the AICCRA-Zambia multi-stakeholder dialogue (MSD) space - Mutenje, Munyaradzi; Jacobs-Mata, Inga (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This video highlights the launch of the CSA-CIS multi-stakeholder dialogue by the AICCRA Zambia project. The launch was held on 9th February 2022 at Southern Sun in Lusaka, Zambia. The objectives of the CSA-CIS multi-stakeholder dialogue space were to: (i) exchange experiences and expertise on climate-smart agriculture and climate information services (CSA-CIS) innovations across public, private and research sectors​; (ii) share insights into the existing multi-stakeholder platforms and processes in the agricultural, livestock, fisheries and water sectors in Zambia​; (iii) identify interests, common goals, commitments and gaps in the CSA MSP space in Zambia; (iv) co-design with participants the agenda for the AICCRA-Zambia MSD Space; (v) develop a framework for operationalizing, monitoring, evaluating and learning of the AICCRA Zambia MSD space, and (vi) explore the most feasible pathways for sustainable and inclusive CSA-CIS scaling in Zambia. Five local SMEs were awarded US$50,000 grant each for scaling CSA-CIS innovations in Zambia at the same event. AICCRA Zambia is a 3-year initiative (2021-2023) led by the International Water Management Institute (IWMI) with funding from the International Development Association (IDA) of the World Bank.